Defragmented image based autostereoscopic 3D displays with dynamic eye tracking - Kim, Sung-Kyu; Yoon, Ki-Hyuk; Yoon, Seon Kyu; Ju, Heongkyu (ELSEVIER SCIENCE BV, 2015)
We studied defragmented image based autostereoscopic 3D displays with dynamic eye tracking. Specifically, we examined the impact of parallax barrier (PB) angular orientation on their image quality. The 3D display system required One adjustment of PB angular orientation with respect to a display panel. This was critical for both image color balancing and minimizing image resolution mismatch between horizontal and vertical directions. For evaluating uniformity of image brightness, we applied optical ray tracing simulations. The simulations took effects of PB orientation misalignment into account The simulation results were then compared with recorded experimental data Our optimal simulated system produced significantly enhanced image uniformity at around sweet spots in viewing zones. However this was contradicted by real experimental results. We offer quantitative treatment of illuminance uniformity of view images to estimate misalignment of PB orientation, which could account for brightness non uniformity observed experimentally. Our study also shows that slight imperfection in the adjustment of PB orientation due to practical restrictions of adjustment accuracy can induce substantial non -uniformity of view images' brightness. We find that image brightness non uniformity critically depends on misalignment of PB angular orientation, for example, as slight as <0.01 in our system. This reveals that reducing misalignment of PB angular orientation from the order of 10(-2) to 10(-3) degrees can greatly improve the brightness uniformity. (C) 2015 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license.
Keywords: VIRTUAL-REALITY DISPLAY; CROSSTALK